Analisis Citra Merek Dalam Meningkatkan Kepuasan Dan Loyalitas Pelanggan Mobil Hilux Di Kabupaten Merauke - Muhammad Awal; Aldisa Arifudin; Restu Monika Nia Betaubun (EKONOMI & SOSIAL, 2022)
The purpose of this study was to analyze brand image in increasing Hilux Car Customer Satisfaction and Loyalty in Merauke Regency. In this study the quantitative method used. This study uses a path analysis model because it has mediating or intermediary variables. From the results of the tests that have been carried out, the results of the first substructure equation explain that there is an influence of brand image on satisfaction of 0.482 and the value of sig 0.000 is smaller than 0.05. Which means that brand image has a big enough influence to make customers feel satisfied. While the second substructure equation has the effect of brand image on customer loyalty of 0.310 and the value of sig 0.001 is smaller than 0.05. And the results of the second substructure equation in the table there is an influence of satisfaction on customer loyalty of 0.502 and the value of sig 0.000 is smaller than 0.05. From the results of the analysis of the direct influence of brand image on customer loyalty of 0.310 while the magnitude of the indirect effect of brand image on customer loyalty through satisfaction is 0.242. It can be seen that the direct effect of brand image on customer loyalty is greater than the indirect effect of brand image on customer loyalty through satisfaction